Effects of four cooking methods on flavor and sensory characteristics of scallop muscle - Wang, Yueyao; Tian, Guifang; Mao, Kemin; Chitrakar, Bimal; Wang, Zhongxuan; Liu, Jie; Bai, Xinzhong; Sang, Yaxin; Gao, Jie (Frontiers in Nutrition, 2022)
Abstract This work aimed to explore the influence of four different cooking methods (Boiling, roasting, frying, and microwaving) on the sensory characteristics of scallop muscles. Headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) and electron nose (e-nose) were combined to analyze the aroma of scallops. Combined with the results of free amino acids and electronic tongue (e-tongue), the taste changes of different samples were analyzed. Furthermore, texture profile and microstructure analysis jointly showed the influence of cooking methods on texture. The results showed that frying was the most suitable cooking method for scallop muscle because it resulted the best tasted products, boiled scallops retain the highest similarity to fresh scallops. Besides, a higher level of lipid oxidation and Maillard reaction resulted in significant increase in aldehydes, ketones, furans, umami, and sweet amino acid. For the boiled sample, the loss of water-soluble compounds and less fat oxidation resulted in fewer flavor substances and free amino acids, along with looser organizational structure and poorer sensory quality. The research showed that besides the texture of scallop muscle, volatile organic compounds and free amino acids as well as their mutual roles in taste and smell were also important to sensory receptivity.